IMPLEMENTASI METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION DALAM PENENTUAN PEMILIHAN GURU TERBAIK - Saut Mahulae (STMIK KAPUTAMA, 2019)
The teacher is one of the most important components possessed by a school in daily activities, which becomes a challenge for the management of educational institutions or schools to be able to provide an appropriate, effective and efficient decision in data management in the increasingly competitive world of competition spurring schools to strive harder to improve the quality of their schools. The Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method is a method that has the concept that the best chosen alternative not only has the shortest distance from a positive ideal solution, but also has the longest distance from a negative ideal solution. The criteria used in this system vary, according to the selection of exemplary teachers provided by the school.